Pemanfaatan Teknologi Informasi Bidang E-Commerce di Toko Mulia Jaya - Afdhal Syafnur; Romy Aulia; Yori Apridonal; Alfan Suhendra; Nur Aisyah Lubis (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2021)
E-commerce or selling electronically is a marketing and sales activity through internet or digital media online. The purpose of this community service activity is to provide an understanding of the role of electronic sales in an effort to increase sales of UMKM products that have an impact on the welfare of business actors and employees and benefit the people who buy their products. Mulia Jaya is a store that sells women's accessories and clothing, such as clothes, shoes, bags, and other women's accessories. Because it is still relatively new, the marketing carried out has not been maximized, namely selling its products to consumers in the surrounding area only, so it has not been able to attract consumers more broadly. This is the goal of this community service activity, namely to provide an understanding of the use of information technology in the field of e-commerce in marketing and selling Toko Mulia Jaya products so as to increase product sales.